Weight Is More Accurate than Gestational Age When Estimating the Optimal Endotracheal Tube Depth in Neonates - Hsien-Kuan Liu; Yung-Ning Yang; Shu-Leei Tey; Pei-Ling Wu; San-Nan Yang; Chien-Yi Wu (MDPI AG, 2021)
Determining the optimal endotracheal tube (ETT) depth in neonates remains challenging for neonatologists. The guideline for optimal ETT depth is based on the patients' weight or gestational age. However, there is a discrepancy in the suggested ETT depth between these two parameters. The aim of this retrospective study was to compare the recommended weight-based and age-based formulas for optimal ETT depth and obtain the optimal reference before intubation. Participants were assigned to group 1 if the recommended ETT insertion depth based on weight was concordant with the recommended depth based on gestational age, and to group 2 if the weight and age-based depth recommendations were discordant. After exclusion, 180 patients were included in the analysis. Results indicated that the predicted ETT depth suggested by age required more adjustment than by weight (p < 0.05). Furthermore, the required adjustment in the weight-based formula was smaller than the age-based formula (p < 0.05). Multivariate linear regression analysis revealed that weight was the key factor affecting the optimal depth (p < 0.001). These results imply that when there is a discrepancy in ETT depth between the weight-based and age-based recommendation, the weight-based one will be more accurate than the age-based one.